Numerical Investigation to the Effect of Suction-Induced Seepage on the Settlement in the Underwater Vacuum Preloading with Prefabricated Vertical Drains - Shu Lin; Dengfeng Fu; Zefeng Zhou; Yue Yan; Shuwang Yan (Journal of Marine Science and Engineering, 2021)
Vacuum preloading combined with prefabricated vertical drains (PVDs) has the potential to improve the soft sediments under water, however, its development is partly limited by the unclear understanding of the mechanism. This paper aims to extend the comprehension of the influential mechanism of overlapping water in the scenario of underwater vacuum preloading with PVDs. The systematic investigations were conducted by small strain finite element drained analyses, with the separated analysis schemes considering suction-induced consolidation, seepage and their combination. The development of settlement in the improved soil region and the evolution of seepage flow from the overlapping water through the non-improved soil region into improved zone are examined in terms of the build-up of excess pore pressure. Based on the results of numerical analyses, a theoretical approach was set out. It was capable to estimate the time-dependent non-uniform settlement along the improved soil surface in response to the combined effects of suction-induced consolidation and seepage. The difference of underwater and onshore vacuum preloading with PVDs is discussed with some practical implication and suggestion provided.